Tinjauan Kritis Terhadap Teori Aktivitas dan Dilema Sosial - Juneman Juneman (Humaniora, 2011)
Nowadays, there are developing theories in social psychology. Two of them are activity and social dilemma theory. Unfortunately, Indonesia has less expertise in specific theoretical social psychology. The article is purposed to give analysis for the two theories including its history, its development today, and also its research critical and prospect in the future. This description could help academics and practitioners to build and develop best theories (as well as practice) in their own environment. Based on the critical analysis, it could be concluded that along with their advantages and limits, both activity and social dilemma theory are prospective in triggering researches especially in Indonesia, where there are not much research using those theories.